Selecting the Right Tool For the Job - Caplan, Arthur L. (Am J Bioeth, 2015)
There are competing ethical concerns when it comes to designing any clinical research study. Clinical trials of possible treatments for Ebola virus are no exception. If anything, the competing ethical concerns are exacerbated in trying to find answers to a deadly, rapidly spreading, infectious disease. The primary goal of current research is to identify experimental therapies that can cure Ebola or cure it with reasonable probability in infected individuals. Pursuit of that goal must be methodologically sound, practical and consistent with prevailing norms governing human subjects research. Some maintain that only randomized controlled trials (RCTs) with a placebo or standard-of-care arm can meet these conditions. We maintain that there are alternative trial designs that can do so as well and that sometimes these are preferable to RCTs.